2015
DOI: 10.1007/s10877-015-9701-z
|View full text |Cite
|
Sign up to set email alerts
|

An improvised pressure gauge for regional nerve blockade/anesthesia injections: an initial study

Abstract: High injection pressure is one of the warning signs of intraneural injection, with animal models suggesting pressures higher than 69 or 176 kPa as high risk, and is normally detected subjectively and inaccurately. We describe a system improvised from common clinical components that uses Boyle's law to objectively measure injection pressure. The objectives of the study were to (1) Validate our improvised pressure gauge (IPG) by comparing the injection pressure as calculated by Boyle's law against the measured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The concept of “half-the-air” to keep injection pressure below 15 psi derives from the reliability of compressed air injection technique [ 22 , 23 ], and the facility-independent half-the-air setting helps popularize injection pressure monitoring in clinical practice by the advantages of low cost, easy assembling, and incorporating a test syringe (ensuring the total mass of local anesthetic to be delivered) and a long (200 cm) extension tube (facilitating the operation for the assistant, thus physical ergonomics) with a low dead space (1.4 mL) [ 9 ]. Thereafter, another improvised pressure gauge was proposed using the fluid meniscus level in the 1 ml syringe in place of D5W syringe as the passive indirect in-line manometer [ 24 ]. However, as with the drawback of the commercial in-line manometer, this improvised pressure gauge lacks a pop-off valve to limit the injection pressure and/or eliminate the initial high peak pressure [ 20 , 24 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of “half-the-air” to keep injection pressure below 15 psi derives from the reliability of compressed air injection technique [ 22 , 23 ], and the facility-independent half-the-air setting helps popularize injection pressure monitoring in clinical practice by the advantages of low cost, easy assembling, and incorporating a test syringe (ensuring the total mass of local anesthetic to be delivered) and a long (200 cm) extension tube (facilitating the operation for the assistant, thus physical ergonomics) with a low dead space (1.4 mL) [ 9 ]. Thereafter, another improvised pressure gauge was proposed using the fluid meniscus level in the 1 ml syringe in place of D5W syringe as the passive indirect in-line manometer [ 24 ]. However, as with the drawback of the commercial in-line manometer, this improvised pressure gauge lacks a pop-off valve to limit the injection pressure and/or eliminate the initial high peak pressure [ 20 , 24 ].…”
mentioning
confidence: 99%
“…Thereafter, another improvised pressure gauge was proposed using the fluid meniscus level in the 1 ml syringe in place of D5W syringe as the passive indirect in-line manometer [ 24 ]. However, as with the drawback of the commercial in-line manometer, this improvised pressure gauge lacks a pop-off valve to limit the injection pressure and/or eliminate the initial high peak pressure [ 20 , 24 ]. In other words, with the in-line manometer only as a monitor, “syringe feel” is still performed at the very beginning of injection.…”
mentioning
confidence: 99%
“…Apart from providing enhanced safety of PNBs, the BSmart offers some advantages such as objective monitoring of injection pressure, warning of high injection pressure, prevention of too forceful and rapid injections, consistent monitoring of resistance to injection regardless of who performs the actual injection, and standardized and objective documentation of injection pressure information. However, such assembly may produce false-positive readings during higher injection flow rates [ 48 ] due to changed injectate flow characteristics from laminar to turbulent flow during rapid injection or the inherent resistance to flow from the needle shaft [ 48 ]. Since this manometer is disposable, it is unknown if its accuracy will degrade with repeated use or if the piston will become less free to move with multiple injections.…”
Section: Reviewmentioning
confidence: 99%
“…In humans, injection pressure monitoring has been shown to give a positive (pathological) signal upon needle‐nerve contact injection against fascial planes , or injection at high speed , suggesting good sensitivity but low specificity for intraneural injection. Following a review of factors associated with the risk of nerve injury after peripheral nerve block, Sondekoppam et al concluded that there is inadequate evidence (low quality) supporting the use of injection pressure monitoring for preventing nerve injury .…”
Section: Towards Introduction Of Pressure Monitors?mentioning
confidence: 99%
“…The experimental setups by Claudio et al and Patil et al which seemed to suggest that physicians are bad at detecting high injection pressures cannot be simply translated to the clinical situation, where dynamic sonographic information on needle‐tip localisation is combined with visual and tactile information during incremental injection of small fluid volumes to confirm needle‐tip location. Whether active measurement of injection pressure curves (or opening injection pressure ) has the potential to elevate patient safety above the level provided by expert use of ultrasound guidance combined with tactile cues and situational awareness (hopefully today's scenario) remains unclear.…”
Section: Towards Introduction Of Pressure Monitors?mentioning
confidence: 99%